Analysis of the effect of resistance increase on the capacity fade of lithium ion batteries. (14th March 2019) - Mandli, Aravinda R.; Kaushik, Anshul; Patil, Rajkumar S.; Naha, Arunava; Hariharan, Krishnan S.; Kolake, Subramanya M.; Han, Seongho; Choi, Wooin
Summary: Lithium ion cells, when cycled, exhibit a two‐stage degradation behavior characterized by a first linear stage and a second nonlinear stage where degradation is rapid. The multitude of degradation phenomena occurring in lithium ion batteries complicates the understanding of this two‐stage degradation behavior. In this work, a simple and intuitive model is presented to analyze the coupled effect of resistance growth and the shape of the state of charge (SOC)‐open circuit voltage (OCV) relationship in representing the complete degradation behavior. The model simulations demonstrate that a single resistance that increases linearly on cycling can capture the transition from slow to fast degradation, primarily due to the shape of the SOC‐OCV curve. Further, the model simulations indicate that the shape of the degradation curve depends strongly on the magnitude of current at the end of discharge of the cycling protocol. To verify these observations, specific experiments are designed with minimal capacity loss but with shrinking operating voltage ranges that result in shrinking operating OCV range. The results of the experiments validate the observations of model simulations. Further, long‐term cycling experiment with a commercial lithium ion cell shows that the operating OCV range shrinks substantially with aging and is a major reason for the observed accelerated degradation. The analysis of the present work provides significant insights towards developing simple semiempirical models suitable for battery life management in microcontrollers. Abstract : "The origin of two‐stage degradation behavior in lithium‐ion batteries is analyzed in this work using both model simulations and experiments. Model simulations suggest and experimental results validate that resistance increase coupled with the shape of the SOC‐OCV curve captures the two‐stage degradation behavior and that the cycling protocol can have a significant effect on the observed capacity fade behavior. The analysis of the present study provides significant insights towards developing simple semiempirical models suitable for charging optimization in microcontrollers."